2008
DOI: 10.1111/j.1460-9592.2008.02448.x
|View full text |Cite
|
Sign up to set email alerts
|

Laryngospasm: review of different prevention and treatment modalities

Abstract: Laryngospasm is a common complication in pediatric anesthesia. In the majority of cases, laryngospasm is self-limiting. However, sometimes laryngospasm persists and if not appropriately treated, it may result in serious complications that may be life-threatening. The present review discusses laryngospasm with the emphasis on the different prevention and treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 69 publications
(119 reference statements)
0
62
1
1
Order By: Relevance
“…The upper airway obstruction, secondary to the laryngeal spasm, is then responsible for a negative-pressure pulmonary edema, consistent with the lung damage observed in our study. Negativepressure pulmonary edema following laryngeal spasm during general anesthesia is a well-recognized but rare complication secondary to upper airway obstruction in human general anesthesia (Alalami et al, 2008). However, in the present study, direct laryngoscopy revealed no adduction of the vocal cords while rats were making inspiratory efforts; therefore no laryngeal spasm was diagnosed.…”
Section: Discussioncontrasting
confidence: 62%
“…The upper airway obstruction, secondary to the laryngeal spasm, is then responsible for a negative-pressure pulmonary edema, consistent with the lung damage observed in our study. Negativepressure pulmonary edema following laryngeal spasm during general anesthesia is a well-recognized but rare complication secondary to upper airway obstruction in human general anesthesia (Alalami et al, 2008). However, in the present study, direct laryngoscopy revealed no adduction of the vocal cords while rats were making inspiratory efforts; therefore no laryngeal spasm was diagnosed.…”
Section: Discussioncontrasting
confidence: 62%
“…Several reasons can explain the low success rate and the high incidence of gastric distension (86.5%) with the standard management of laryngeal spasm. Attempts to provide positive-pressure ventilation with a face mask may distend the stomach, splinting the diaphragm, thus delaying hypoxia resolution [19,20]. Additionally, in complete spasm, positive pressure ventilation may make the situation worse by forcing the area just above the false cords against each other closing the entrance to the larynx [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with several studies that demonstrate significantly higher rates of both reactive airway and laryngospasm in young children. [27][28][29] The distribution of laryngospasm also corresponds to the age distribution of the study sample, in which 85.0% of pediatric patients seen by American Society of Dentist Anesthesiologists dentist anesthesiologists were age 6 and younger, 12.0% were between the ages of 7 and 12, and 4% were between the ages of 13 and 18 ( Figure). Thus, the incidence of laryngospasm is distributed proportionally across all ages in this sample, consistent with patterns seen in previously published studies.…”
Section: Discussionmentioning
confidence: 99%